Indonesia - Nigeria Strategic Cooperation: An Indonesia's Perspective - Mardialina, Mala; Munir, Ahmad Mubarak (Nation State: Journal of International Studies, 2020)
Indonesia-Nigeria cooperation resumed since President Gus Dur made an official visit to Nigeria in 2000. Indonesia relations became increasingly constructive by creating several trade agreements with the Nigerian government and formulating Indonesia-Africa Forum (IAF) is a real constructive strategy in focusing on Indonesia’s Foreign Policy toward the Africa region. There are more than 15 Indonesian companies operating in Nigeria and Nigeria was Indonesia's largest trade partner in Africa with a total volume of trade at USD 1.5 billion in 2019. In the oil sector, Indonesia has a trade deficit with Nigeria but not in the non-oil sector, Nigeria became the entry point for Indonesian products to other African regions. This research is qualitative research using a political cooperation concept as an analytical tool by looking at the dynamics of the Indonesia-Nigeria relationship in the framework of strategic cooperation. The data is gained from a focused review of relevant theories, literature, and previous research findings of the discussed topic. Besides, the data were taken from books, journals, reports, and websites.